Okadaic acid mimics a nuclear component required for cyclin B-cdc2 kinase microinjection to drive starfish oocytes into M phase (The Rockefeller University Press, 1991)
G2-arrested oocytes contain cdc2 kinase as an inactive cyclin B-cdc2 complex. When a small amount of highly purified and active cdc2 kinase, prepared from starfish oocytes at first meiotic metaphase, is microinjected into Xenopus oocytes, it induces activation of the inactive endogenous complex and, as a consequence, drives the recipient oocytes into M phase. In contrast, the microinjected kinase undergoes rapid inactivation in starfish oocytes, which remain arrested at G2. Endogenous cdc2 kinase becomes activated in both nucleated and enucleated starfish oocytes injected with cytoplasm taken from maturing oocytes at the time of nuclear envelope breakdown, but only cytoplasm taken from nucleated oocytes becomes able thereafter to release second recipient oocytes from G2 arrest, and thus contains M phase-promoting factor (MPF) activity. Both nucleated and enucleated starfish oocytes produce MPF activity when type 2A phosphatase is blocked by okadaic acid. If type 2A phosphatase is only partially inhibited, neither nucleated nor enucleated oocytes produce MPF activity, although both do so if purified cdc2 kinase is subsequently injected as a primer to activate the endogenous kinase. The nucleus of starfish oocytes contains an inhibitor of type 2A phosphatase, but neither active nor inactive cdc2 kinase. Microinjection of the content of a nucleus into the cytoplasm of G2-arrested starfish oocytes activates endogenous cdc2 kinase, produces MPF activity, and drives the recipient oocytes into M phase. Together, these results show that the MPF amplification loop is controlled, both positively and negatively, by cdc2 kinase and type 2A phosphatase, respectively. Activation of the MPF amplification loop in starfish requires a nuclear component to inhibit type 2A phosphatase in cytoplasm.